The utilisation of the Internet to market small tourism businesses - R. Elliott; C. Boshoff (South African Journal of Business Management, 2005)
The tourism sector has been identified as an industry that has the potential to make a substantial contribution to the growth of the South African economy. The majority of tourism ventures are, however, small businesses, which differ from their larger counterparts not only in terms of size, but also in regard to access to resources and marketing expertise. Not surprisingly, one of the Issues identified as preventing this sector from reaching its full potential is access to markets. The Internet has been identified as tool which may assist small businesses in both their global and domestic marketing.The focus of this study was to identify the factors specific to the Internet (rather than the technology per se or organisational factors) driving the success of the use of the Internet for marketing purposes in small businesses operating in the tourism sector in South Africa. If these factors can be identified and their relative influence on Internet marketing success be determined, it will allow small tourism businesses utilise the capabilities of the Internet more effectively.The results indicate that having a product champion in the business, having a network of effective alliances, a high level of owner-manager involvement in the Internet marketing strategy as well as a clear owner-manager vision are important to the successful use of the Internet for the marketing of small tourism businesses in South Africa.
Keywords: 650